Diagnosis of filariasis on cytology: a series of 24 cases. (April 2014) - Handa, Uma; Kundu, Reetu; Singhal, Niti; Mohan, Harsh
Filariasis has a worldwide distribution, with a special predilection for tropical and subtropical areas. The microfilaria wanders in lymphatics and can be accidentally trapped in the needle during fine-needle aspiration cytology, thus leading to its incidental detection. This is a retrospective study of 24 cases of microfilarial infestation diagnosed on cytology. Accurate recognition and detection of the parasite leads to the institution of specific treatment and prevents chronic manifestations of the disease.